“Plan de ejercicios pliométricos para deportistas futbolistas de la selección estudiantil de la Universidad Nacional de Chimborazo en el período marzo - julio 2016” - Naula Cuñas, Patricia Mercedes (2017)
Football or soccer is an interchanging sport by high intensity actions like sprints, jumps and fluctuations of direction favored to a great extent by the increase of the strength and power in the lower extremities, factors that can be determinant to achieve sporty success. in the diagnosis carried out on the soccer players of the National University of Chimborazo, no muscle lesions were detected. Nonetheless, certain strength limitations in the extensor musculature of the lower train were notice during the execution of the vertical jump, as well as, horizontal jump which represents an important risk factor. Consequently, the current project has the main objective to design exercise plan of plymetric exercises to prevention muscle injuries in the lower extremities in members of the National University of Chimborazo soccer team during the period from March to July 2016. A Plyometric exercises plan was designed, adequate to the necessities and particularities of the study subjects. In order to gauge the application and experimental study of longitudinal cut was created. The nature of the investigation was clearly quantitative. A population of 30 members of the selection of the National University of Chimborazo team is chosen which represented 100% of the total population. Additionally, protocols were designed and used to execute vertical and horizontal jumps.